Unconventional magnetization plateaus in a Shastry-Sutherland spin tube - Manmana, S. R.; Picon, J. -D.; Schmidt, Kai Phillip; Mila, F. (EPL - Europhysics Letters, 2011)
Using density matrix renormalization group (DMRG) and perturbative continuous unitary transformations (PCUTs), we study the magnetization process in a magnetic field for all coupling strengths of a quasi-1D version of the 2D Shastry-Sutherland lattice, a frustrated spin tube made of two orthogonal dimer chains. At small inter-dimer coupling, plateaus in the magnetization appear at 1/6, 1/4, 1/3, 3/8, and 1/2. As in 2D, they correspond to a Wigner crystal of triplons. However, close to the boundary of the product singlet phase, plateaus of a new type appear at 1/5 and 3/4. They are stabilized by the localization of bound states of triplons. Their magnetization profile differs significantly from that of single-triplon plateaus and leads to specific NMR signatures. We address the possibility to stabilize such plateaus in further geometries by analyzing small finite clusters using exact diagonalizations and the PCUTs. Copyright (C) EPLA, 2011